Proximate, Mineral and Vitamin Contents of Indian Major Carp - Paul, B. N.; Chanda, S.; Sridhar, N.; Saha, G. S.; Giri, S. S. (Indian Journal of Animal Nutrition, 2018)
The variation in proximate composition, mineral and vitamin content was determined in relation to different body weight groups of Indian major carp viz., rohu (Labeo rohita), catla (Catla catla) and mrigal (Cirrhinus mrigala). The samples were collected from different places of West Bengal, Odisha, Karnataka and Chattisgarh and were grouped as 1-50 g, 51-500 g, 501-2000 g and >2000 g. The moisture content was higher (P<0.05) in >2000 g group of rohu and mrigal when compared to catla. The contents of protein, lipids and total ash were similar in all the major carp irrespective of weight groups. Calcium content was higher (P<0.05) in rohu and mrigal in all the weight groups. Sodium, potassium and iron contents were more (P<0.05) in >2000 g group of rohu when compared to others. The Zn content of rohu of 51-500 g group was higher (P<0.05) vis-Ã -vis other groups. Mrigal of size groups 1-50 g and >2000 g contained the highest content of vitamin A. The vitamin D level was higher (P<0.05) in 1-50 g of rohu and 51-2000 g groups of mrigal.